Autocatalysed oxidative modifications to 2-oxoglutarate dependent oxygenases - Mantri, M; Zhang, Z; McDonough, M; Schofield, C (2012)
Ferrous iron and 2-oxoglutarate-dependent oxygenases and related enzymes catalyse a range of oxidative reactions, possibly the widest of any enzyme family. Their catalytic flexibility is proposed to be related to their nonhaem iron-binding site, which utilizes two or three protein-based ligands. A possible penalty for this flexibility is that they may be more prone to oxidative damage than the P450 oxidases, where the iron is arguably located in a more controlled environment. We review the evidence for autocatalysed oxidative modifications to 2-oxoglutarate-dependent oxygenases, including the recently reported studies on human enzymes, as well as the oxidative fragmentations observed in the case of the plant ethylene-forming enzyme (1-aminocyclopropane-1-carboxylic acid oxidase). © 2012 FEBS.